“Caminhar perguntando”: para além, apesar ou com o estado?: A construção de autonomias nos movimentos de economia solidária de Brasil e México - Oliveira, Gustavo Moura de (Universidade do Vale do Rio dos Sinos, 2021)
This thesis presents an analysis of the trajectory of solidary economy movements in Brazil and Mexico from 1995 to 2020, based on their relations and interactions with the State in each of countries. My main interest was guided by the attempt to understand how the autonomy of each movement changed over the time. As this is a qualitative investigation, in order to achieve the objective of the present comparative case study, I carried out a literature review and field research based on participant observations and semi-structured interviews. Regarding the observations, they were carried out both in the scope of the Brazilian Solidarity Economy Movement and in the Mexican Solidarity Economy Movement; 12 representatives of each of the movements were interviewed, plus 4 linked to the state institutions of the Brazilian solidary economy and another 4 with the same type of link in the Mexican case. From the point of view of analysis, the bibliographical investigation would lead me to at least four starting assumptions: autonomy as an individual and collective capacity for lucidity and reflection, as a landmark of action, as a properly relational category and marked by a double process of denial-construction. Based on this, it was possible to think about it in relation to the State from three distinct possibilities: autonomous action beyond the State (denial of its totality and construction of ways to organize life in common on its margins); autonomous action despite the State (denial of its dynamics of functioning and construction of extra-institutional political confrontations aimed at recognizing rights); and autonomous action with the State (denial of its policies and construction of others from institutional participation). The aforementioned typology would end up serving as a framework for empirical analysis in the crossing of data on the movements trajectories with the contextual configurations of each of countries over time. As for the contexts, from the 2000s onwards, Brazil joined other South American experiences and experimented with democratic-participatory governments that opened the State to participation. Mexico, in turn, did not follow this wave and remained almost the entire period analyzed under contexts that were not very attractive to participation. In relation to the trajectories of the movements, in the Brazilian case, the presence of an integrating political-collective subject nationally legitimized by the movement as a whole allowed us to perceive a transit between actions beyond and with the State; within the latter, it oscillated between inserted and interdependent autonomy. In the Mexican case, the absence of that collective political subject added to the disjointed and non-systematic interactions of one or another subject of the movement with the State was what characterized, a type of action beyond the State, also considering the national level. The absence of the aforementioned subject capable of uniting the movement nationally would guide my analytical focus towards the diversity of local experiences. With this focus, it was possible to perceive experiences that were registered both as beyond, as despite and with the State. Finally, it is important to note that, considering the transforming powers of the three dynamics of autonomous action, it seems to be only the one beyond the State that is able to pre-figure in the now, in the present time, the substantive selforganization of life in common which reconnects the economic and political dimensions of life in the everyday-community, as in the case of the Mexican Zapatista Movement.
Keywords: Autonomia; Estado; Movimentos sociais; Economia solidária; Brasil; México; Autonomy; State; Social movements; Solidarity economy; Brazil; Mexico; ACCNPQ::Ciências Humanas::Sociologia